Impact of different planting date on shoot growth and tuber development of white Guinea yam grown in Guinea Savanna - Iseki, K.; Olaleye, O.; Matsumoto, R. (Informa UK Limited, 2024)
White Guinea yam is a tuber crop characterized by a long growth period over the entire rainy season, which is affected by changes in rainfall patterns owing to climate change. In this study, we investigated the effects of shifting the planting date of yam seed tubers on shoot growth and tuber development, which could be a plausible measure for adapting to changes in rainfall patterns. Our results revealed that tuber enlargement in plants with different planting dates started depending on the days after planting rather than the day of the year. This indicates that day length had little effect on tuberization. The final tuber yield was rarely affected by low rainfall during the early growth stage, whereas severe yield reduction occurred when the rainfall stopped during the tuberization period. We conclude that shifting the planting date backward to adjust for delayed rainy seasons increases the risk of severe yield reduction.